Basic and Clinical Aspects of Non-neuronal Acetylcholine: Overview of Non-neuronal Cholinergic Systems and Their Biological - Significance Koichiro Kawashima; Takeshi Fujii (Elsevier, 2008)
Acetylcholine (ACh) is a phylogenetically ancient molecule involved in cell-to-cell signaling in almost all life-forms on earth. Cholinergic components, including ACh, choline acetyltransferase, acetylcholinesterase, and muscarinic and nicotinic ACh receptors (mAChRs and nAChRs, respectively) have been identified in numerous non-neuronal cells and tissues, including keratinocytes, cancer cells, immune cells, urinary bladder, airway epithelial cells, vascular endothelial cells, and reproductive organs, among many others. Stimulation of the mAChRs and nAChRs elicits cell-specific functional and biochemical effects. These findings support the notion that non-neuronal cholinergic systems are expressed in certain cells and tissues and are involved in the regulation of their function and that cholinergic dysfunction is related to the pathophysiology of certain diseases. They also provide clues for development of drugs with novel mechanisms of action. Keywords:: acetylcholine, choline acetyltransferase, non-neuronal cholinergic system, muscarinic receptor, nicotinic receptor